2014
DOI: 10.1016/j.jcrs.2013.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Correction of moderate corneal astigmatism during cataract surgery: Toric intraocular lens versus peripheral corneal relaxing incisions

Abstract: Toric IOLs and PCRIs both reduced astigmatism; however, toric IOLs reduced astigmatism to a higher extent and they were more predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 31 publications
3
50
3
3
Order By: Relevance
“…Previous studies had shown the regression of astigmatism reduction of PCRIs after surgery,27 28 and our 3-month postoperative results might not be sufficiently long enough to show a significant astigmatic regression in the LRI group. Knowing that the astigmatic regression can be as much as 1.00 D,22 it may be anticipated that the fading effect of LRI in our study would be more prominent in long term postoperatively. We also noted that in spite of comparable postoperative UCVA and spherical equivalent, there was a difference in need for glasses in the postoperative period.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies had shown the regression of astigmatism reduction of PCRIs after surgery,27 28 and our 3-month postoperative results might not be sufficiently long enough to show a significant astigmatic regression in the LRI group. Knowing that the astigmatic regression can be as much as 1.00 D,22 it may be anticipated that the fading effect of LRI in our study would be more prominent in long term postoperatively. We also noted that in spite of comparable postoperative UCVA and spherical equivalent, there was a difference in need for glasses in the postoperative period.…”
Section: Discussionmentioning
confidence: 69%
“…However, the authors noted that since the asphericity component was added to the newer versions of toric IOLs after the study, these modified toric IOLs would likely improve the overall visual performance. In a randomised study by Hirnschall et al ,22 30 patients received toric IOL (Rayner T-Flex, Rayner Intraocular Lenses) in one eye and a non-toric version of the same IOL platform (C-Flex or Superflex) combined with 1 or 2 PCRI in the contralateral eye. The results showed that the mean astigmatism vector reduction in the toric IOL group was significantly higher than in the PCRI group.…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in surgical techniques, IOL designs and biometry are maximising the potential of correction of toric IOLs 3 20. Hirnschall et al 21 showed in a comparative study of 60 eyes of 30 patients that toric IOLs could reduce astigmatism to a higher extent, and were more predictable than peripheral corneal relaxing incisions. Other options for astigmatism correction mainly include excimer-laser correction as a second intervention after IOL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Today, toric lenses have been designed because such type of surgeries have been inadequate particularly in the cases with highdegree astigmatism and were proven to effectively correct corneal astigmatism. [14][15][16][17][18] In addition to eyeglass-free near vision provided by multifocal toric intraocular lenses manufactured recently for cataract cases with corneal astigmatism, it has been also possible to correct corneal astigmatism. Postoperative successful outcomes depend on certain factors in multifocal toric IOL implantation same as toric IOL implantation.…”
Section: Discussionmentioning
confidence: 99%